Power supply for domestic gas boilers from inverters with modified sinusoid - Solovei, I.; Plonka, I. (Energy and Automation, 2026)
The article discusses the features of powering domestic gas boilers from autonomous power sources based on inverters with a modified sine wave. The electrical characteristics of such inverters and their impact on the operation of the main components of modern boilers are analyzed: circulation pumps, fans, electronic control boards, and ignition systems. The risks of using non-sinusoidal voltage are identified, in particular, increased heating of electric motors, incorrect operation of sensors and automation units, and increased electromagnetic interference. The purpose of the study is to assess the impact of the output voltage waveform of an inverter with a modified sine wave on the start-up and stable operation modes of domestic gas boilers, as well as to determine the effectiveness of using a filter to reduce higher harmonic components and to justify the admissibility of using such a backup power source.An analysis of the output voltage of an inverter with a modified sine wave was performed using an inductive filter of higher harmonics from the standpoint of reducing higher harmonic components in the voltage curve, by simulating this process using the EWB 32 electronic workbench application. The feasibility of using inverters with a modified sine wave to ensure stable and safe operation of gas boilers in conditions of power supply interruptions was substantiated. Practical recommendations for the selection and operation of backup power supply systems in domestic conditions were proposed.The proposed method of using an inverter with a modified sine wave and an additional induction filter has advantages over existing methods. It allows the use of inexpensive inverters to power domestic gas boilers, ensuring energy efficiency and reliability of their operation.Recieved: 15.01.2026.  Recieved: 19.03.2026. Accepted: 17.04.2026.
Keywords: gas boiler; inverter; modified sine wave; harmonic distortion; induction filter; asynchronous motor; autonomous power supply; electromagnetic compatibility